2019
DOI: 10.1016/j.nbd.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

DLK regulates a distinctive transcriptional regeneration program after peripheral nerve injury

Abstract: Following damage to a peripheral nerve, injury signaling pathways converge in the cell body to generate transcriptional changes that support axon regeneration. Here, we demonstrate that dual leucine zipper kinase (DLK), a central regulator of injury responses including axon regeneration and neuronal apoptosis, is required for the induction of the pro-regenerative transcriptional program in response to peripheral nerve injury. Using a sensory neuron-conditional DLK knockout mouse model, we show a time course fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 89 publications
(124 reference statements)
1
97
0
Order By: Relevance
“…These studies suggest that SCI may elicit a transcriptional response in DRG, but a detailed analysis of how SCI affect gene expression in DRG and sensory neurons has not been performed in detail. To better understand the transcriptional response in DRG after SCI and SNI, we performed RNA-seq of L4 DRG one day (1d) after SCI and analyzed our results with a previously generated RNA-seq data set collected 1d after SNI ( Fig 1A ; 16 ). We found that SCI elicits a less robust transcriptional response in the DRG compared to SNI, with fewer differentially expressed (DE) genes compared to SNI ( Fig 1B, Supplementary Table 1,2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggest that SCI may elicit a transcriptional response in DRG, but a detailed analysis of how SCI affect gene expression in DRG and sensory neurons has not been performed in detail. To better understand the transcriptional response in DRG after SCI and SNI, we performed RNA-seq of L4 DRG one day (1d) after SCI and analyzed our results with a previously generated RNA-seq data set collected 1d after SNI ( Fig 1A ; 16 ). We found that SCI elicits a less robust transcriptional response in the DRG compared to SNI, with fewer differentially expressed (DE) genes compared to SNI ( Fig 1B, Supplementary Table 1,2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of RATFs is believed to arise in part from retrograde transport of kinases from the injury site back to the cell soma 18,19 . The dual leucine zipper kinase DLK is required for retrograde injury signaling and induction of RATF after nerve injury 16,20 , and is significantly decreased after SCI (0.29 fold, p-adj < 0.05). To determine if the limited transcriptional upregulation of RATF’s after SCI relates to decreased levels of DLK, we used previously generated RNA-seq data that examined the transcriptional response to nerve injury in mice lacking DLK (DLK KO; 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this notion, injury to the mature mammalian PNS results in NMNAT2-dependent degeneration of severed distal axons (Beirowski et al 2005), just as in RGCs. However, while the somal response to injury is DLK-dependent in both RGCs and DRG neurons in vivo, in the former system DLK upregulates pro-apoptotic mediators (Watkins et al 2013), while in the latter it upregulates several Regeneration Associated Genes to facilitate axon regeneration (Shin et al 2012;Shin et al 2019). ZDHHC17-dependent palmitoylation of DLK and NMNAT2 thus has the potential to ensure appropriate somal and distal axon responses to injury in diverse neuron types, even when the 'downstream' functional outcome differs.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating the expression of regeneration-associated genes (RAGs) has become an attractive strategy for the development of therapeutic applications that restore neuronal connectivity ( 1 , 2 ). Comparative analysis of transcriptome has revealed highly promising targets for manipulation to effectively enhance axon regeneration ( 3 6 ). This approach has also led to the identification of signaling pathways regulating axon regeneration, such as the MAPK, JAK/STAT, BMP/Smad, and PTEN/mTOR pathways ( 7 12 ).…”
mentioning
confidence: 99%